2014
DOI: 10.5007/2175-7925.2014v27n2p79
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade larvicida de extratos obtidos do caule de Croton linearifolius Mull. Arg. (Euphorbiaceae) sobre larvas de Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae)

Abstract: Submetido em 24/07/2013 Aceito para publicação em 12/03/2014 ResumoDentre os problemas de saúde pública que acometem a população humana, em nível nacional e mundial, destaca-se a dengue, cujo principal vetor do vírus é o Aedes aegypti (Linnaeus, 1762). Para a redução da densidade populacional desse vetor, recomenda-se o controle integrado e, como parte desse controle, o uso de inseticidas. No entanto, tal prática tem levado à seleção de populações de insetos resistentes. Dessa forma, faz-se necessário buscar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The data of this work are in agreement with the results presented by Silva et al (2014), where these authors evidenced that the plant extracts demonstrated potentially promising with regard to the larval control of A. aegypti.…”
Section: Resultssupporting
confidence: 92%
“…The data of this work are in agreement with the results presented by Silva et al (2014), where these authors evidenced that the plant extracts demonstrated potentially promising with regard to the larval control of A. aegypti.…”
Section: Resultssupporting
confidence: 92%
“…In these tests, damage to the anal papillae and midgut epithelial tissue was observed in addition to larval death (Elumalai et al, 2016). In the study by Silva et al (2014) in which the larvicidal activity of the ethanolic extract of the stem of Croton linearifolius Mull. Arg.…”
Section: Discussionmentioning
confidence: 99%
“…The eggs were then kept in a BOD incubator, and the hatchability was checked every five days until the 25 th day of the experiment. The eggs exposed to water and 1% DMSO were used as the negative control (Silva et al, 2014), while a commercial insecticide (0.02% Imiprotin, 0.05% Permetrin, and 0.1% Esbiotrin) was used as the positive control. All assays were performed in triplicates (Nunes et al, 2015).…”
Section: Ovicidal Activitymentioning
confidence: 99%